2023
DOI: 10.1111/1346-8138.16905
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional human papillomavirus vaccine for the treatment of recalcitrant cutaneous warts

Efrat Bar‐Ilan,
Jonathan Bar,
Avital Baniel
et al.

Abstract: Human papillomavirus (HPV) is ubiquitously distributed in the population worldwide and its most frequent clinical presentation is cutaneous warts. Despite various treatment options currently available, many patients experience persistent and refractory disease. We sought to evaluate the clinical effectiveness and safety profile of intralesional HPV 9‐valent vaccine for the treatment of recalcitrant warts. A retrospective study was performed for all cases of cutaneous warts treated with intralesional 9‐valent H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Additionally, it was recently reported that the 9vHPV vaccine as an intralesional treatment led to 60% of patients achieving complete resolution of the disease. Intriguingly, unlike intramuscular vaccination, where a younger age was linked to a more favorable response, the intralesional administration showed that advanced age was associated with an improved score ( p < 0.05, β of −0.044 [confidence interval, −0.083 to −0.004]) for wart clearance [ 4 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, it was recently reported that the 9vHPV vaccine as an intralesional treatment led to 60% of patients achieving complete resolution of the disease. Intriguingly, unlike intramuscular vaccination, where a younger age was linked to a more favorable response, the intralesional administration showed that advanced age was associated with an improved score ( p < 0.05, β of −0.044 [confidence interval, −0.083 to −0.004]) for wart clearance [ 4 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…HPV vaccines consist of noninfectious particles that resemble HPV and originate from the L1 capsid protein, which is unique to each subtype of HPV. Notably, there is homology between the L1 capsid proteins found in HPV subtypes associated with common warts, such as HPV subtypes 1–4, and those present in HPV vaccines [ 4 , 10 ]. This similarity may potentially trigger cross-immunity, eliciting an immune response against a broad range of HPV subtypes, including those leading to AGW.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations